Alleviation of Salinity Stress in Peanut by Application of Endophytic Bacteria - Pal, Kamal K.; Dey, Rinku; Sherathia, Dharmesh N.; Devidayal,; Mangalassery, Shamsudheen; Kumar, Arvind; Rupapara, Rupal B.; Mandaliya, Mona; Rawal, Priya; Bhadania, Roshani A.; Thomas, Manesh; Patel, Mili B.; et al. (Frontiers in Microbiology, 2021)
The development of salinity affects 7% of the world’s land surface, acting as a major constraint to crop productivity. This study attempted to use the co-evolving endophytes of peanut to alleviate salinity stress and enhance the yield of peanut. Diverse and different tissue colonizing endophytes were isolated from peanut and screened in vitro by seed germination bioassay imposing gradients of salinity, with two cultivars TG37A (susceptible) and GG2 (moderately resistant), in potted conditions using saline irrigation water. Finally, nine endophytes capable of producing IAA and ACC-deaminase, promoting root growth and yield in potted conditions were selected for further evaluation in field conditions. They were evaluated with saline water (1.5–2.0 dS/m) in saline soil with susceptible cultivar TG37A. Simultaneously, three endophytes (Bacillus firmus J22N; Bacillus tequilensis SEN15N; and Bacillus sp. REN51N) were evaluated with two cultivars, GG2 and TG37A, during rainy and post-rainy seasons with elevated salinity. The application of endophytes like Bacillus firmus J22N and Bacillus sp. REN51N enhanced the pod and haulm yield of peanuts by 14–19% across cultivars, salinity, and seasons. In addition, there was significant modulation in parameters like relative water content; production of enzymes like superoxide dismutase (SOD), glutathione reductase (GR), catalase (CAT), ascorbate peroxidase (APX), lipid peroxidase (POD), and H2O2 content in leaf; and uptake of potassium. The activities of the enzymes involved in scavenging reactive oxygen species (ROS) increased with salinity, and further increased with endophytes like Bacillus firmus J22N, Bacillus tequilensis SEN15N, and Bacillus sp. REN51N. There was an enhanced accumulation of proline, reduced level of phenol and H2O2, and enhanced uptake of potassium with the inoculation of endophytes. This improved scavenging capacity of plants by endophytic modulation of ROS scavengers, uptake of K, production of ACC deaminase and IAA, root and biomass growth, modulation in relative water content, and enhanced accumulation of osmoprotectant might be the reasons of alleviation of salinity stress. Endophytes could have alleviated salinity stress in peanuts, indicating the mechanisms and potential of peanuts at the field level. These endophytes could be applied to bring agricultural sustainability to salinity-affected areas in the future. Furthermore, few genera viz. Kocuria, Brevundimonas, Agrococcus, Dietzia, and Kytococcus were observed in peanut tissue for the first time.